PENDAMPINGAN KEGIATAN TAHJIZUL JENAZAH BAGI MASYARAKAT DI DUSUN BATU LANGGAR PALALANGAN KECAMATAN CERMEE KABUPATEN BONDOWOSO - Moh.Faizin; Maughfiro Umrotus Zakiyah; Siti Fatimah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Assisting in the preparation of the deceased is one form of community service aimed at enhancing the understanding and skills of the community in handling the deceased according to Islamic law. This activity was carried out in Dusun Batu Langgar Palalangan, Cermee District, Bondowoso Regency, involving the local community as the main participants. The main issue found is the low understanding of the community regarding the procedures for handling corpses, which leads them to still rely on religious leaders or local clerics. The method used in this activity is Participatory Learning and Action (PLA) through socialisation, training, direct practice, and activity evaluation. The results of the activity show an increase in the community's understanding and ability to bathe, shroud, pray for, and bury the deceased according to Islamic law. The enthusiasm of the participants during the activities indicates that the mentoring program is running effectively and has a positive impact on the community's readiness to perform fardhu kifayah. This activity is expected to foster a community that is self-sufficient in the implementation of tahjizul jenazah and to enhance the religious awareness of the community.